Tibio-pedal arterial pressure assessment during endovascular intervention to improve quality-of-life in patients with intermittent claudication - Kwan, Tak W.; Lee, Samuel; Lin, Patricia; Liou, Michael; Siu, Henry; Patel, Apurva; Ruzsa, Zoltan (Frontiers in Cardiovascular Medicine, 2022)
Physiological assessment of peripheral arterial lesions is infrequently performed during endovascular interventions. The aim of this study is to compare the quality-of-life (QOL) outcomes and the tibio-pedal arterial pressure post-endovascular intervention. This is a retrospective study of 343 patients who had successful tibio-pedal accesses. The average tibio-pedal arterial pressure at baseline was 87.0±32.9 mmHg vs. 135.5±30.2 mmHg post-intervention (p<0.05). Average baseline and 30-day WIQ scores were summation (99.8±3.3 vs. 115.0±3.1, p < 0.05), walking distance (35.7±1.3 vs 42.5±1.3, p < 0.05), walking speed (21.1±0.9 vs. 23.6±0.8, p = 0.036), stair climbing (4.7±1.4 vs. 24.2±1.4, p = 0.019), and symptoms (18.8±0.2 vs 20.1±0.2, p < 0.05), respectively. When comparing the increased post-intervention tibio-pedal arterial pressure <60 mmHg vs. > 60 mmHg, the average delta WIQ scores were all significantly improved with summation (10.0±3.9 to 25.8±5.5, p=0.01), walking distance (4.1±1.7 to 9.8±2.5, p=0.02), walking speed (1.5±1.1 to 4.3±1.5, p=0.02), stair climbing (2.3±1.8 to 9.4±2.5, p=0.02), and symptoms (1.0±0.3 to 1.8±0.4, p=0.04), respectively. We conclude that increasing the post-intervention tibio-pedal arterial pressure by 60 mmHg can enhance QOL as suggested by improvement of WIQ scores.